Isolamento e caracterização de enzimas ligninolíticas expressas pelos fungos Chaetomium cupreum URM 5066 e Mucor racemosus CBMAI 847 - Dionizio, Bruna Soares (Universidade Federal de São Carlos, 2018)
The degradation of lignin, which together with cellulose and hemicellulose constitutes the cell wall of plants, is generally hampered by its complex structure, its high molecular weight and its insolubility. However, fungi are able to degrade the lignocellulosic biomass by employing specific enzymes such as Laccases, Manganese peroxidases and Lignin peroxidases. This work aimed to identify and purify ligninolytic enzymes produced by four fungi: Mucor racemosus CBMAI 847, Penicillium oxalicum CBMAI 1996, Penicillium sp. FPZSP 151 and Chaetomium cupreum URM 5066. Through plaque activity using ABTS as substrate it was observed that C. cupreum and M. racemosus are the best producers of oxidases. The two fungi were then selected and cultivated in liquid medium, with the highest values of enzymatic activity observed on the 7th day of growth for both, and presenting 37.50±2.67 U L-1 for C. cupreum and 0.231±0.007 U L-1 for M. racemosus. It was possible to purify four enzymes present in the crude extract of M. racemosus, which have activity with veratryl alcohol, indicating that they may be lignins peroxidases. Three oxidases present in the crude extract of C. cupreum were purified and characterized, which have activity with substrates ABTS and SYR, at least one of the enzymes belonging to the subclass of laccases. Qualitative tests demonstrated that the enzymes produced by C. cupreum fungus were capable of degrading lignin. The results obtained in this work show that the fungi M. racemosus and C. cupreum are ligninolytic enzymes producers and that C. cupreum fungus has great potential for application in biotechnological processes, acting in the degradation of lignins. Moreover this is the first time that a purification of oxidases enzymes expressed by these fungi is reported.
Isolation and characterization of ligninolytic enzymes expressed by fungi Chaetomium cupreum URM 5066 and Mucor racemosus CBMAI 847
Keywords: Chaetomium cupreum URM 5066; Mucor racemosus CBMAI 847; Enzimas ligninolíticas; Lignina peroxidase; Lacase; Chaetomium cupreum URM 5066; Mucor racemosus CBMAI 847; Ligninolytic enzymes; Lignin peroxidase; Laccase; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS::PROTEINAS